Effect of benign prostatic hyperplasia surgery on ejaculatory function - M. P. Dianov; P. S. Kyzlasov; A. G. Martov; P. N. Korolev; V. A. Perepechay; V. V. Khvorov (Вестник урологии)
Introduction. There are a wide range of techniques available for the removal of hyperplastic prostate tissue. However, the choice of method rarely considers its eﬀect on ejaculatory function.Objectives. To evaluate the eﬀect of surgery for benign prostatic hyperplasia (BPH) by endovideosurgical posterior adenomectomy (EVS AE) and transurethral electroenucleation of the prostate (TUEB) on copulatory function and its ejaculatory component.Materials & methods. Sixty sexually active patients aged 58 to 78 years with indications for surgical treatment of BPH were included in the study. The patients were randomized into two equal groups. The ﬁrst group (30 patients) underwent EVS AE by standard technique without preservation of the prostatic urethra. The second group (30 patients) underwent TUEB. Before treatment, standard questionnaires used in urologic practice were completed: IIEF-5, IPSS-QOL, and the scale of quantitative assessment of male copulatory function (scale “MCF”). The block of questions speciﬁcally characterizing the ejaculatory component and the "Male Sexual Health Questionnaire", namely the section " Ejaculatory function domain", were analyzed separately. The assessment was conducted before treatment and at the 12th week following surgery. No signiﬁcant diﬀerences were found between the groups on any of the questionnaires prior to surgery.Results. Three months following surgery, there was a signiﬁcant improvement in the IPSS-QOL scores for the EVS AE group, by 24 points and 4.3, respectively, and for the TUEB group, 25.6 points and 4.3 (both p < 0.0001). No change was observed in the IIEF-5 questionnaire (p > 0.05). A slight reduction in scores was noted on the MCF scale for the TUEB group (by 2.9 points, p < 0.05), indicating that the general state of erectile function remained unchanged. However, reductions were seen in the "MCF — Ejaculatory Component" and "Male Sexual Health Questionnaire — Ejaculatory function domain" scales for the TUEB group, with ballpark scores decreasing by 3.2 and 6.8 points, respectively (both p = 0.0326 and p = 0.0254), indicating a worsening in ejaculatory function following TUEB treatment.Conclusion. When selecting a speciﬁc surgical approach for BPH management, consideration should be given to the patient's tolerance for the degree of invasiveness of the procedure while preserving ejaculatory function, and adherence to a treatment strategy that aligns with the patient's individual preferences and expectations.